LATE PLEISTOCENE-HOLOCENE LITHOFACIES - PALEOGEOGRAPHIC CHARACTERISTICS IN BA LAT RIVER MOUTH - Nghi, Tran; Tuyen, Nguyen Thi; Thanh, Dinh Xuan; Trang, Nguyen Thi Huyen; Nhan, Tran Thi Thanh; Thai, Nguyen Dinh; Chuan, Le Viet; Long, Nguyen Hoang (Vietnam Journal of Marine Science and Technology, 2017)
Lithofacies and paleogeographical characteristics of late Pleistocene-Holocene deposits are related to three sedimentary system tracts: Lowstand systems tract (LST) corresponds to the low regressive phase from 50 ka BP to 18 ka BP. The sedimentary accumulative space is situated from the boundary of weathering crust to the 100 m water depth. In Ba Lat rivermouth area, the lowstand systems tract is dominated by the alluvial silty sand facies group (arLST); Transgressive systems tract (TST) in Ba Lat rivermouth area constitutes a lithofacies section including three facies in upward direction as follows: (1) Transgressive alluvial silty - sand facies (atTST). (2) Transgressive estuary sandy - mud facies (amtTST). (3) Lagoonal maximum transgressive greenish clay facies (mtTST); Highstand systems tract (HST) in the downstream Red river delta area constitutes a deltaic plain structure consisting of three parts: High subaerial delta, low subaerial delta and subaqueous delta, which had been formed from 5 ka BP.